Searches for the baryon- and lepton-number violating decays B0→Λ+cl−, B−→Λl−, and B−→Λl[bar]− - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
Searches for B mesons decaying to final states containing a baryon and a lepton are performed, where the baryon is either Λc or Λ and the lepton is a muon or an electron. These decays violate both baryon and lepton number and would be a signature of physics beyond the standard model. No significant signal is observed in any of the decay modes, and upper limits in the range (3.2-520)×10−8 are set on the branching fractions at the 90% confidence level.